2015
DOI: 10.1080/08897077.2014.988323
|View full text |Cite
|
Sign up to set email alerts
|

Expected Problem Drinker Possible Self: Predictor of Alcohol Problems and Tobacco use in Adolescents

Abstract: Background Alcohol and tobacco use commonly co-occur in adolescents. According to the cross-substance facilitation of information processing hypothesis, cognitive structures related to one substance increase use of another related substance through enhanced cognitive processing. In this study, we test this hypothesis by determining whether a problem drinker “possible self” in 8th grade predicts alcohol and tobacco use in 9th grade. Methods A secondary data analysis of a 12-month longitudinal dataset was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
2
16
1
2
Order By: Relevance
“…These findings suggest that even the slightest acknowledgment that drinking will become an important part of oneself in the future is associated with early experimentation with alcohol. Using the same measure in a sample of eighth graders, a future‐oriented drinker identity predicted not only alcohol problems 1 year later but also tobacco use 1 year later …”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings suggest that even the slightest acknowledgment that drinking will become an important part of oneself in the future is associated with early experimentation with alcohol. Using the same measure in a sample of eighth graders, a future‐oriented drinker identity predicted not only alcohol problems 1 year later but also tobacco use 1 year later …”
Section: Literature Reviewmentioning
confidence: 99%
“…Whereas the developmental trajectory of a drinker identity has not been examined, we believe that having a future‐oriented drinker identity motivates early alcohol use, and over time, alcohol use itself leads to development of a well‐developed current drinker identity that leads to a sustained pattern of high levels of alcohol use and alcohol problems. Using the same dataset from an adolescent study reported earlier in this paper, we were able to take a preliminary look at this. As shown in Table , of the 137 adolescents in the sample, only 18 defined themselves in terms of drinking.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Some investigators have focused on properties of the total collection of possible selves, e.g., the number of hoped-for (Black, Stein, & Loveland-Cherry, 2001), number of feared (Oyserman & Markus, 1990a), number of expected (Aloise-Young et al, 2001), and number of balanced pairs (a hoped-for and feared possible self in the same domain, e.g., a hoped-for possible self to graduate from high school and a feared possible self of not graduating from high school; Aloise-Young et al, 2001; Oyserman & Markus, 1990a, 1990b). Other investigators have focused on a single possible self, e.g., presence or absence of a possible self in a specific content domain including alcohol use, e.g., “problem drinker” (Corte & Szalacha, 2010; Lee et al, in press), binge drinker (Quinlan, Jaccard, & Blanton, 2006), or the content domain of the most important possible self (Hooker & Kaus, 1992). …”
Section: Possible Selvesmentioning
confidence: 99%